Ensaios com unidades armazenadoras modulares a nível de fazenda - del Giudice, Paulo Mário; Coelho de Alvarenga , Sônia (Revista Ceres, 2025)
An «EXPERIMENTAL PROGRAM» was designed to test the viability and analyze the economic and technical implications of farm corn storage systems. The development and use of such information could have implications on a large scale in the system. To accomplish this objective a storage unit was designes for corn. To conduct the experiment two storage units were designed: one for ear corn and the other for shelled corn. Three units were constructed on the campus of the Federal University of Viçosa: one for shelled corn and two for ear corn. On farms in a town 55 kilometers from the university, three isolated units for ear corn were built in order to conduct the research under farm field conditions.